Public Policy Frames and Gender mainstreaming: an analysis of childcare policy in Brazil during the left turn (2003-2016) - Mazzini Marcondes, Mariana; Ferreira Santos Farah, Marta; Alves, Mário Aquino (Organizações & Sociedade, 2021)
Brazil was one of the countries that integrated Latin America’s left turn, a period in which social policies have become central. During the Labor Party’s Government (Partido dos Trabalhadores) (2013-2016), were developed institutional conditions to mainstream gender in public policies, which embraced the issue of the sexual division of labor. However, did it mean an effective reorientation of the childcare policy towards gender equality perspectives? This article aims to reflect upon this question, drawing on the gender mainstreaming concept. It is understood as a process of incorporation of feminist perspectives into the public policy framing, regarding the (re)definition of both the public problem and the course of state action. To do so, we carried out a qualitative study of gender mainstreaming on childcare policy (daycare centers and leaves), focusing on official discourses, mainly through documentary analysis. Based on the results analyzed, we identified the coexistence of two frames: “education and childcare rights” and “promotion of women’s economic autonomy”. Since the first one has prevailed, we conclude that gender mainstreaming was marginal in the childcare policy, during the analyzed period.